Inpatient Unit Leaders’ Perspectives on Parent Engagement in Neonatal and Pediatric Intensive Care - Vance, Ashlee J. (Adv Neonatal Care, 2021)
BACKGROUND: Hospital unit leaders help set the unit’s priorities and are responsible for guiding the unit mission and philosophy of care; however, the perspective of leaders in facilitating parent engagement within intensive care units is limited. PURPOSE: The purpose of this study was to explore how medical and nursing unit leaders facilitate parent engagement in intensive care settings. METHODS: Qualitative secondary analysis of 16 semistructured interviews of unit leadership (medical directors and nurse managers). Directed content analysis explored themes within the interviews using systematic strategies to ensure rigor. FINDINGS: Unit leadership described 3 main features of care delivery necessary for supporting parent engagement: (1) culture of care, (2) relationships in care, and (3) environment of care. Communication among providers and parents and timing of decision-making were key areas addressed, along with concerns about physical space limiting parent engagement. Unit leaders discussed how the 3 main features (unit culture, relationships, and physical space) of care delivery were interconnected to optimize parent engagement. IMPLICATIONS FOR PRACTICE: Overall, unit leaders recognized the importance of each feature of care delivery in facilitating engagement. Parent engagement is ultimately influenced by the optimization of delivering inclusive care: the physical space, the policies surrounding medical and nursing care, and the overall culture of the unit. IMPLICATIONS FOR RESEARCH: Future research needs to explore best practices around relationship building and managing space limitations. Further clarification of the needs and expectations of both parents and providers surrounding parent engagement in intensive care settings is needed.